The Potential of Taro Village in Supporting Sustainable Tourism in Gianyar, Bali - Wijaya, Nyoman Surya; Sudarmawan, I Wayan Eka (Journal of Business on Hospitality and Tourism, 2020)
The development of rural tourism requires the participation of local communities in the entire development phase starting from the planning, implementation and supervision stages. However, in reality there is Often neglect of community participation. This study aims to examine the strategy of developing Taro Rural Tourism and the involvement of local communities in development. The research in this paper was conducted in the tourist village of Taro, Gianyar Regency, Bali. Data collection is done by literature study, in-depth interviews and non-participant observation. The analytical method used is descriptive analysis. This paper shows that the development of tourist villages in Taro can still be developed considering that Taro still has tourism potential that is very possible to be developed.